KEWENANGAN PEMERINTAH DAERAH DALAM PERIZINAN BANGUNAN TERHADAP ALIH FUNGSI BANGUNAN PERUMAHAN MENJADI TEMPAT USAHA TERKAIT RENCANA TATA RUANG WILAYAH: (Studi di Kota Baru Gresik) - Mayasari, Fitria (JURNAL MEDIA HUKUM DAN PERADILAN, 2018)
This article aims to know and analyze the legislation of the implementation of the authority of Gresik District Government of the functional shift of the residential building into a business place in Gresik Kota Baru housing which does not match with the spatial plan of the region.The result of the research indicates that the national legislation is sufficient in balancing the building arrangement of Gresik Kota Baru housing, in terms of regional policy with the regulation of Gresik regency number 6/ 2017 on building permit (IMB) is expected that the community before adding, changing and building new buildings then first must have permission. The execution of the shift of building function in Gresik Kota Baru housing has not fully owned building permit that matches with the current building. Regarding to the issue the local government in its authority is to regulate and to balance the arrangement of buildings in the Gresik Kota Baru housing so that people have a building permit which is in accordance with the current building.